2016
DOI: 10.18295/squmj.2016.16.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Stress among Saudi Arabian Dermatology Patients: Cross-sectional study

Abstract: abstract:Objectives: This study aimed to determine the prevalence of depression, anxiety and stress among Saudi Arabian dermatology patients and to assess associations with sociodemographic and clinical characteristics. Methods: This cross-sectional study was conducted among 300 consecutive dermatology patients visiting King Abdulaziz Medical City in Riyadh, Saudi Arabia, in August 2015. The Arabic version of the Depression, Anxiety and Stress Scale was used to screen for symptoms of depression, anxiety and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 19 publications
3
38
3
3
Order By: Relevance
“…Most available data regarding the impact of AD on patient quality of life (QoL) in the Middle East is from Saudi Arabia. Numerous studies have reported that QoL is significantly affected in Saudi Arabian patients with dermatologic diseases, including AD [ 53 56 ]. Abolfotouh et al reported data from 283 adult Saudi Arabian patients with skin disease who completed the Skindex-16 scale, which assesses QoL across symptom, emotional, and functional domains [ 53 ].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Most available data regarding the impact of AD on patient quality of life (QoL) in the Middle East is from Saudi Arabia. Numerous studies have reported that QoL is significantly affected in Saudi Arabian patients with dermatologic diseases, including AD [ 53 56 ]. Abolfotouh et al reported data from 283 adult Saudi Arabian patients with skin disease who completed the Skindex-16 scale, which assesses QoL across symptom, emotional, and functional domains [ 53 ].…”
Section: Quality Of Lifementioning
confidence: 99%
“…and Dowlatshahi et al ., have indicated that depression is more common among people with skin disorders than in the general population. Previous studies have indicated that around 30–50% of skin disorder patients tend to suffer from depression . A multicenter cross‐sectional study of 13 European countries estimated that the prevalence of psychiatric comorbidity among dermatological patients was 30%, while 10.1% of these suffered from depression .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that around 30-50% of skin disorder patients tend to suffer from depression. [12][13][14][15][16] A multicenter cross-sectional study of 13 European countries estimated that the prevalence of psychiatric comorbidity among dermatological patients was 30%, while 10.1% of International Journal of Dermatology 2018, 57, 284-290 ª 2018 The International Society of Dermatology these suffered from depression. 9 The presence of depressive symptoms tends to be associated with poor prognostic indicators, and thus the effect of the skin disorder upon the patient's quality of life is a major predictor of possible psychological problems as compared to the severity of the skin problem itself.…”
Section: Introductionmentioning
confidence: 99%